2014
DOI: 10.2298/apt1445011d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bread dough mixing method on rye bread quality

Abstract: The objective of this study was to evaluate the effect of sourdough (indirect bread dough mixing method) on the quality of rye/wheat bread (TYPE 500 wheat flour and whole grain rye flour - 60:40) and determine its advantages over the straight dough method. Three bread dough mixing methods were used: I - indirect bread dough mixing using flour scalding; II - indirect bread dough mixing without flour scalding; III - straight dough mixing. The study involved the monitoring of the following: micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, it was found that rye scald significantly affected the crumb cell diameter and area, as more cells per slice area could be obtained [40]. A lower pH in fermented rye scald may cause peptization and swelling of the proteins in the flour, increasing the consistency and subsequently the dough's ability to retain carbon dioxide [50]. It has also been claimed that as the acidity rises, all of the moisture in the dough is bound by the undegraded starch, which may have an impact on mass loss after baking [51].…”
Section: Bread Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was found that rye scald significantly affected the crumb cell diameter and area, as more cells per slice area could be obtained [40]. A lower pH in fermented rye scald may cause peptization and swelling of the proteins in the flour, increasing the consistency and subsequently the dough's ability to retain carbon dioxide [50]. It has also been claimed that as the acidity rises, all of the moisture in the dough is bound by the undegraded starch, which may have an impact on mass loss after baking [51].…”
Section: Bread Qualitymentioning
confidence: 99%
“…Gao et al (2018) observed higher sensory scores of rye-wheat breads made with heat-treated rye flour [40]. Djukic et al (2013) reported that with the addition of rye scald to bread dough, the sensory qualities of the rye/wheat bread were enhanced [50]. Higher scores of bitterness for breads with Sc and FSc could be explained by the presence of wholemeal flour, which contains bitter taste-eliciting bran [59].…”
Section: Sensory Properties and Overall Acceptability Of Bread Samplesmentioning
confidence: 99%
“…The most typical way of baking rye bread is to use sourdough method, which has several advantages against straight-dough method (Djuki c et al, 2014). Sourdough originated acidity improves the baking quality of rye, which is mostly based on the swelling and degradation of cell walls, arabinoxylans, and proteins during fermentation.…”
Section: Baking Quality Of Ryementioning
confidence: 99%